The social competence of swimming instructor - Anna Wiśniewska (Nicolaus Copernicus University in Toruń, 2016)
Introduction. Sport in our times is becoming part of the lifestyle in the growing number of people in different social groups and this activity is participated in every age. It is important that the instructor had the competence or personality dispositions that determine the effectiveness of the task in hand . Aim of the study. The aim of this article is identify the role of social skills in work as swimming instructor . Methods and materials.   The studies is based on qualitative research inquiries. In the article analyzed views and studies relating to issues within the scope of this article. Results. Social competences are a group of skills necessary to establish a relationship of partnership in the sport. Conclusions. The lack of social competence, if not impossible, then at least significantly hinders the achievement of the activities of learning to swim.